Human Septal Cartilage Tissue Engineering: Current Methodologies and Future Directions - Tammy B. Pham; Robert L. Sah; Koichi Masuda; Deborah Watson (Bioengineering)
Nasal septal cartilage tissue engineering is a promising and dynamic field with the potential to provide surgical options for patients with complex reconstruction needs and mitigate the risks incurred by other tissue sources. Developments in cell source selection, cell expansion, scaffold creation, and three-dimensional (3D) bioprinting have advanced the field in recent years. The usage of medicinal signaling cells and nasal chondroprogenitor cells can enhance chondrocyte proliferation, stimulate chondrocyte growth, and limit chondrocyte dedifferentiate. New scaffolds combined with recent innovations in 3D bioprinting have allowed for the creation of more durable and customizable constructs. Future developments may increase technical accessibility and manufacturability, and lower costs, to help incorporate these methods into pre-clinical studies and clinical applications of septal cartilage tissue engineering.